The fascist authoritarian model of illiberal democracy - Dunwoody, Philip T.; Gershtenson, Joseph; Plane, Dennis L.; Upchurch-Poole, Territa (Frontiers in Political Science, 2022)
Based on our observations and scholarship about how democratic norms are currently being undermined, we propose a model of fascist authoritarianism that includes authoritarianism, the production and exaggeration of threats, conspiracy-oriented propaganda adoption, and distrust of reality-based professions. We refer to this as the Fascist Authoritarian Model of Illiberal Democracy (FAMID) and argue that all components are essential for understanding contemporary antidemocratic movements. We demonstrate that all components of FAMID correlate with illiberal antidemocratic attitudes, that Republicans generally score higher than Democrats on the model components, and that all components significantly contribute to predicting illiberal antidemocratic attitudes. We find approximately equal support for both left-wing and right-wing illiberal antidemocratic attitudes. The fascist authoritarian model of illiberal democracy helps explain the basic mechanisms by which an authoritarian leader works to erode liberal democratic norms—and does a better job at doing so than simpler authoritarianism theories.